2018
DOI: 10.1080/00498254.2018.1467065
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics reveal aryl hydrocarbon receptor (Ahr)-regulated lipid metabolic pathway in alpha-naphthyl isothiocyanate (ANIT)-induced intrahepatic cholestasis

Abstract: 1. Ultra-performance liquid chromatography coupled with electrospray ionization quadrupole mass spectrometry (UPLC-ESI-QTOF MS)-based lipidomics was employ to elucidate new mechanism of alpha-naphthyl isothiocyanate (ANIT)-induced intrahepatic cholestasis in mice. 2. Multiple lipid components significantly increased in ANIT-induced intrahepatic cholestasis, including PC 16:0, 20:4, PC 16:0, 22:6, PC 16:0, 18:2, LPC 18:2, PC 18:2, LPC 18:1, PC 18:1, 14:0, SM 18:1, 16:0, oleoylcarnitine, and palmitoylcarnitine. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Furthermore, a lipidomic study of ANIT-induced intrahepatic cholestasis uncovered the role of the aryl hydrocarbon receptor (AHR) in regulating expression of choline kinase (CHK) in mice. Knockout of the Ahr gene significantly reversed ANIT-induced lipid metabolism via Chka expression, and reversed the intrahepatic cholestasis [96]. Vascular protein sorting-associated protein 33B (VPS33B) is involved in the trafficking of intracellular proteins to distinct organelles.…”
Section: Cholestasismentioning
confidence: 99%
“…Furthermore, a lipidomic study of ANIT-induced intrahepatic cholestasis uncovered the role of the aryl hydrocarbon receptor (AHR) in regulating expression of choline kinase (CHK) in mice. Knockout of the Ahr gene significantly reversed ANIT-induced lipid metabolism via Chka expression, and reversed the intrahepatic cholestasis [96]. Vascular protein sorting-associated protein 33B (VPS33B) is involved in the trafficking of intracellular proteins to distinct organelles.…”
Section: Cholestasismentioning
confidence: 99%
“…Lipid species of these plasma samples were measured using Ultraperformance liquid chromatography coupled with electrospray ionization quadrupole mass spectrometry (UPLC-ESI-QTOF MS) system in Tianjin University. The application studies of this system were shown in previous published papers 19,20 . Firstly, 10 μl of plasma was added to 10 μl of mixed standard solution (containing μg/mL 19:0-19:0 PC, 10 μg/mL 17:0-17:0 PE, 15 μg/mL 12:0 SM, 2μg/mL 19:0 Lyso PC, or 10μg/mL 19:0 ceramide dissolved in isopropanol-acetonitrile solution).…”
Section: Study Protocolmentioning
confidence: 99%
“…However, the mechanisms underlying ANIT-induced acute cholestasis have remained to be fully elucidated. Due to its similarities with drug-induced cholangiolitic hepatitis in humans, ANIT-induced acute cholestasis has been widely used as a model of acute cholestasis in susceptible species, such as rats (15)(16)(17).…”
Section: Itraq-based Quantitative Proteomics Analysis Of the Hepatoprotective Effect Of Melatonin On Anit-induced Cholestasis In Ratsmentioning
confidence: 99%